2015
DOI: 10.1530/jme-14-0226
|View full text |Cite
|
Sign up to set email alerts
|

P2X7 receptors: role in bone cell formation and function

Abstract: The role of the P2X7 receptor (P2X7R) is being explored with intensive interest in the context of normal bone physiology, bone-related diseases and, to an extent, bone cancer. In this review, we cover the current understanding of P2X7R regulation of bone cell formation, function and survival. We will discuss how the P2X7R drives lineage commitment of undifferentiated bone cell progenitors, the vital role of P2X7R activation in bone mineralisation and its relatively unexplored role in osteocyte function. We als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 127 publications
0
42
0
Order By: Relevance
“…et al, 2017). The P2X7R is widely expressed in diverse tissues, including hematopoietic cells (Feng et al, 2016), neurons (Miras-Portugal et al, 2017), glia (Stokes et al, 2015;Kaczmarek-Hajek et al, 2018), bone (Agrawal and Gartland, 2015), muscle (Fabbrizio et al, 2019), endothelium (Green et al, 2018), epithelium (Woods et al, 2012), and immune cells (Ferrari et al, 1997). In the exocrine pancreas, P2X7Rs have been shown to be primarily expressed in pancreatic ductal cells where they may contribute to secretory regulation through induction of cation fluxes and interaction with cholinergic signaling (Novak et al, 2010;Burnstock and Novak, 2012).…”
Section: The Role Of P2 Receptors In Salivary Gland Functionmentioning
confidence: 99%
“…et al, 2017). The P2X7R is widely expressed in diverse tissues, including hematopoietic cells (Feng et al, 2016), neurons (Miras-Portugal et al, 2017), glia (Stokes et al, 2015;Kaczmarek-Hajek et al, 2018), bone (Agrawal and Gartland, 2015), muscle (Fabbrizio et al, 2019), endothelium (Green et al, 2018), epithelium (Woods et al, 2012), and immune cells (Ferrari et al, 1997). In the exocrine pancreas, P2X7Rs have been shown to be primarily expressed in pancreatic ductal cells where they may contribute to secretory regulation through induction of cation fluxes and interaction with cholinergic signaling (Novak et al, 2010;Burnstock and Novak, 2012).…”
Section: The Role Of P2 Receptors In Salivary Gland Functionmentioning
confidence: 99%
“…Studies suggested that the Glu496Ala polymorphism of P2X7 receptor is responsible for ATP‐mediated apoptosis in osteoclast (Ohlendorff et al, ). In addition, ATP may cause the disruption of osteoclastic cytoskeleton and the reduction of osteoclasts survival and resorption by initiation of apoptosis (Agrawal & Gartland, ; Miyazaki et al, ). Contradictorily, another study showed that P2X7 antagonists KN‐62 can potently induce the apoptosis of human primary osteoclasts by activating caspase‐3 and inhibiting interleukin‐6 (IL‐6) production (Penolazzi et al, ).…”
Section: The Effect Of P2x7 Receptor On Bone Diseasesmentioning
confidence: 99%
“…The activation of P2X7 receptors stimulates the release of proinflammatory cytokines, such as interleukins and tumor necrosis factor-alpha (TNF-α). Therefore, P2X7 receptors play a crucial role in inflammation, immunity, neurological function, and apoptosis 11, 12 . Accordingly, P2X7 receptors are potential therapeutic candidates for rheumatoid arthritis, hypertension, and atherosclerosis 13, 14 , and clinical trials of chemical compounds targeting P2X7 have been conducted for P2X7-associated diseases 15 .…”
Section: Introductionmentioning
confidence: 99%